Chuquisaca, 1880 to 1930: declining elites, rural resistances and economic changes in Southern Bolivia - Rodrigues, Andre Figueiredo [UNESP] (2024)
The book Se pavonean en los pueblos: resistencia rural y modernidad en Chuquisaca (1880-1930), , by the American historian Erick Langer, examines the economic changes and rural resistances experienced in Southern Bolivia, notably in the Chuquisaca department, between the years 1880 and 1930, at the time of the decline of silver mining and the rise of tin mining. It historicized the impoverishment of local and regional elites and their strategies to maintain their fortunes, by buying indigenous communal lands, modernizing properties in the districts of Yamparaez, Cinti, Tomina and Azero and confronting resistance from rural workers. The complexity of the responses to these economic stimuli enters one of the most important moments in Bolivian history: the decline of silver mining at the end of the 19th th century.